At forholde sig professionelt: Pædagogens professionsdannelse som eksemplarisk case - Hammershøj, Lars Geer; Henriksen, Morten (Tidsskrift for Professionsstudier, 2022)
The aim of the article is to present the concept professional Bildung and use it to throw light on the professionalism of the social educator. The assumption is that Bildung as a form of character formation will be highly relevant in the labor market in the future. Professional Bildung is a concept for this and is defined as the capacity to relate professionally in one’s work. Based on a presentation of the concept, we analyze acts on educational aims and discussions of professionalism of the social educator. Furthermore, we analyze examples of relating creatively and innovatively as a social educator from project LegeKunst, which aims at promoting play and Bildung through art and culture. In the discussion, we argue that the professionalism of the social educator is exemplary for professional Bildung in the sense that the social educator relates to open situations and exercise judgment. Furthermore, the analysis of LegeKunst indicates that relating creatively and innovatively concerns the readiness of the social educator to play along and change his or hers educational practice. At the end, we compare these findings with the professionalism of the teacher, which appears to differ from the social educator in that teaching to a larger degree includes specific professional tasks and goals.